Bundle to care for newborn children of mothers with suspected or confirmed diagnosis of COVID-19 - Maria Paula Custódio Silva; Nylze Helena Guillarducci Rocha; Cinthia Lorena Silva Barbosa Teixeira; Flávia da Veiga Ued; Mariana Torreglosa Ruiz; Divanice Contim (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To build and validate the contents of a bundle for the care of newborn children of mothers with suspected or confirmed diagnosis of COVID-19 in the delivery room and in the rooming-in care. Method Methodological research, developed in 2020 in three stages: bibliographic survey, construction of the instrument in Google Forms® and content validation by seven judges. The initial instrument consisted of seven nursing care. The content validity index above 80% was used to assess the agreement between the judges. Results All items in the bundle reached agreement among judges above 80% after the third round of evaluation. The final version consisted of six items. Conclusion This study allowed the construction and content validation of the proposed bundle. The content proved to be valid and may contribute to the quality of nursing care in the face of the care of these newborns.